Project management of business development in the context of digitalisation - A. A. Perfilyev; F. F. Sharipov; М. A. Dyakonova (Управление)
The relevance of this study is determined by the fact that economic science lacks an integrated approach to develop a methodology for managing business development projects in digital conditions for companies working in the science-intensive field, for example, in e-commerce. The study partially fills this gap, which in turn allows to develop methods, tools, indicators of assessment of the business development project management in the digital conditions for the companies that work in the field of e-commerce, relevant in terms of the great challenges of the global economy, to solve theoretical and practical problems of modernisation of the economy and innovative development of the Russian Federation (hereinafter referred to as RF). It defines the scientific and practical significance of the project. As a subject of the study, the digitalisation of projects of Chinese and Russian enterprises and organisations of the international trade between the RF and China is considered. The objectives are, first, to examine the process of digitalisation of projects of the Chinese and Russian enterprises and organisations of the field of business cooperation between Russia and China and, second, to propose a set of recommendations for increasing the quality and quantity of the successful projects.